Extending the GERG-2008 equation of state: Improved departure function and interaction parameters for (methane + butane). (June 2016) - Rowland, Darren; Hughes, Thomas J.; May, Eric F.
Highlights: The GERG-2008 EOS was tested against recently published low temperature data for (methane + butane). A simpler departure function reduced the maximum cp deviation at T = 120 K from (110 to 7) %. Improved BIPs for (methane + butane) were determined by re-fitting to an extended data set. Deviations for high pressure VLE data at T = 244 K were reduced from (9 to 1.4) %. Abstract: The Groupe Européen de Recherches Gazières (GERG) 2008 multi-parameter equation of state (EOS) is considered the reference model for the prediction of natural gas mixture properties. However, the limited quality of thermodynamic property data available for many key binary mixtures at the time of its development constrained both its range of validity and achievable uncertainty. The data situation for the binary system (CH4 + C4 H10 ) in particular was identified previously as limiting the ability of the GERG-EOS to describe rich natural gases at low temperatures. Recently, new vapour-liquid equilibrium (VLE) and liquid mixture heat capacity data measured at low temperatures and high pressures have been published that significantly improve the data situation for this crucial binary, allowing erroneous literature data to be identified and the predictive behaviour of the GERG-EOS when extrapolated to be tested. The 10 basis functions in the generalised departure function used by the GERG-EOS for several binaries including (CH4 + C4 H10 ) were examined to eliminate the term causing a divergence between measured and predicted liquid mixture isobaric heat capacities at T < 150 K. With a simplified nine-term departure function, the maximum relative deviation between the measured and predicted heat capacities was reduced from nearly (110 to 7) %. The interaction parameters in the GERG equation were also re-determined by including, for the first time for this binary, reliable low temperature VLE data together with most of the other high temperature data used in the original development of the model. The new interaction parameters for (CH4 + C4 H10 ) reduced the relative deviation of bubble point pressures measured and calculated at T = 244 K from (9 to 1.4) %, without affecting the accuracy of property predictions at higher temperatures.